1994
DOI: 10.1111/j.1440-1681.1994.tb02438.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Cytotoxic Lymphocyte Granule Serine Proteases Activate Target Cell Endonucleases to Trigger Apoptosis

Abstract: Upon interaction with target cells, cytotoxic T lymphocytes and natural killer cells vectorially secrete highly specialized cytoplasmic granules containing perforin and a family of serine proteases (granzymes). This granule exocytosis mechanism of cytolysis is of patho-physiological importance, and usually results in target cell DNA fragmentation. Neither perforin nor granzymes possess inherent nuclease activity, but in combination they can induce target cell apoptosis. Perforin forms transmembrane pores in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Alternatively, many of the proteases/nucleases may actually have a downstream function to fully degrade and recycle macromolecules following cell death. Also, it has been suggested that the means by which proteases could contribute to chromatin cleavage would be to activate nucleases themselves, freeing them from an inhibitory complex or conformation (19,52).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, many of the proteases/nucleases may actually have a downstream function to fully degrade and recycle macromolecules following cell death. Also, it has been suggested that the means by which proteases could contribute to chromatin cleavage would be to activate nucleases themselves, freeing them from an inhibitory complex or conformation (19,52).…”
Section: Discussionmentioning
confidence: 99%
“…Lamin A, lamin B, poly(ADPribose) polymerase, and topoisomerases are all targets of proteolytic degradation during apoptosis in many systems (39,47,48). As is the case for protein B23, nucleolin is another nuclear matrix protein that is localized to the nucleolus and involved in rRNA synthesis and has been shown to be a preferential target of serine proteases during programmed death induced in target cells by cytotoxic lymphocytes (49). Although the nature of the proteases responsible for degradation of these nuclear matrix proteins, including protein B23, is still unknown, a Ca 2ϩ -dependent protease exists in the nuclear lamina (39) and may be involved in this process (40).…”
Section: Fig 2 Effect Of Androgen Deprivation On Steady-state Level Ofmentioning
confidence: 99%
“…Inhibition of granzyme proteolytic activity blocks perforin-dependent pore formation in both hemolytic assays and NK cell-mediated assays (12). Granzymes also initiate the procaspase apoptotic cascade leading to a second type of granule-initiated target cell death, apoptosis (13,14). After granule-mediated necrosis or apoptosis, the killer cell is unharmed, suggesting that a protective mechanism remains to be discovered.…”
Section: Perforin Lytic Activity Is Controlled By Calreticulinmentioning
confidence: 99%